THE RELATION BETWEEN TURNOVER INTENTION, HIGH PERFORMANCE WORK PRACTICES (HPWPs), AND ORGANISATIONAL COMMITMENT: A STUDY AMONG PRIVATE HOSPITAL NURSES IN MALAYSIA - Aizzat Mohd Nasurdin,; Tan Cheng Ling,; Sabrina Naseer Khan, (Asian Academy of Management Journal, 2018)
Turnover poses a serious threat in healthcare settings. The scarcity of healthcare professionals and particularly nurses is highlighted as one of the biggest obstacles to achieving health system efficiency and effectiveness. As such, healthcare administrators need to search for ways to retain qualified and competent nurses. This study provides a framework depicting how organisational commitment can mediate the relationship between three forms of high performance work practices (HPWPs) (performance appraisal, compensation, and employment security) and turnover intention. Statistical analysis using partial least squares (PLS) conducted on questionnaire data from 639 staff nurses working in private hospitals in Malaysia revealed that two forms of HPWPs (performance appraisal and compensation) lead to reduced turnover intention via organisational commitment. Finally, the implications of our findings, limitations, and future research suggestions are discussed.